(untitled) (Journal of Contemporary Philology, 2018)
The semantic category of gradation belongs to the rare categories functioning both at the level of proposition and its arguments. Its surface exponents are adverbs and adjectives, the objects of the evaluation are appropriately constitutive members of propositions and their arguments. The Slavic languages inherited the “classical” semantic paradigm of three components: positive, comparative and superlative and adapted their surfaceexponents to their evolving grammatical models. The development of these languages brought about some new semantic types of gradient evaluation. The constructions that attract attention are those which link the means of evaluation with its future planned application. They are present in both analyzed languages, but are more frequently used in Macedonian and its multilingual environment, hence the answer for the problem stated in the title of the paper is in favor of Macedonian.